Aiskrim Cik Su / Syamsulina Mohd Sahit - Mohd Sahit, Syamsulina (2021)
Aiskrim Cik Su owned by Suryati binti Mohd Sahit. The owner gets the idea to sell the Aiskrim Cik Su based on ice cream Malaysia that very popular at the past. But the owner makes some revolution which is she makes the variety flavor to the ice cream. Besides that, Aiskrim Cik Su not only sell the Malaysian ice cream only. The owner also sells the ice cream inside the jar to make people more interact with the product. The Aiskrim Cik Su was establish in 2 years which is starting in 2019. Initially, the owner just trying to produce the ice cream just for the hobby but because of she looks that the ice cream become popular, she starts to selling the ice cream as the part time job. Even she already working, she still wants to produce and sell the ice cream to get the side income. Aiskrim Cik Su have more than 10 flavors of ice cream Malaysia and 10 flavor of ice cream jar. The business is totally conducted by herself and family. Her children helping her to produce the ice cream and her brother and sister become her agent to sell the product. The service to this product is delivery based on the area and the payment via online and cash. The owner also promoting her product using media social platform which is Facebook and Whatsapp.